Cocaine-induced gene regulation in D1 and D2 neuronal ensembles of the nucleus accumbens - Philipp Mews; Autumn VA Mason; Emily G. Kirchner; Molly Estill; Eric J. Nestler (Communications Biology)
Abstract Cocaine use disorder is characterized by persistent drug-seeking behavior and a high risk of relapse, driven in part by lasting molecular and circuit adaptations in the nucleus accumbens. To explore the transcriptomic changes underlying these alterations, we employed fluorescence-activated nucleus sorting coupled with single-nucleus RNA sequencing to analyze D1 and D2 medium spiny neurons in this brain region of male mice subjected to acute cocaine exposure or to prolonged withdrawal from repeated cocaine exposure without or with an acute cocaine rechallenge. This approach allowed us to precisely delineate and contrast transcriptionally distinct neuronal subpopulations─or ensembles─across various treatment conditions. We identified significant heterogeneity within both D1 and D2 MSNs, revealing distinct clusters with unique transcriptional profiles. Notably, we identified a discrete D1 MSN population characterized by the upregulation of immediate early genes, as well as another group of D1 MSNs linked to prolonged withdrawal, uncovering novel regulators of withdrawal-related transcriptome dynamics. Our findings provide a high-resolution transcriptomic map of D1 and D2 MSNs, illustrating the dynamic changes induced by cocaine exposure and withdrawal. These insights into the molecular mechanisms underlying cocaine use disorder highlight potential targets for therapeutic intervention aimed at preventing relapse.